Low THD Grid Connected Converter Under Variable Frequency Environment - Rabia Nazir; Alan R. Wood; Aqsa Shabbir (IEEE Access, 2019)
This paper is aimed at achieving unity power factor and low total harmonic distortion (THD) at the input side of a grid connected three-phase rectifier in a variable grid frequency environment. Variable grid frequency results in performance degradation of the digital controllers. Advanced repetitive control (ARC) scheme is an internal model principal-based digital control scheme, capable of tracking a variable frequency signal with nearly constant and very low (nearly zero) steady-state error. The ARC is a Taylor series expansion-based digital repetitive controller whose parameters can be tuned online with reasonably fast transient response to track the signal with an updated frequency. In this paper, the ARC has been applied to a three-phase grid connected rectifier where the reference frequency is variable. Controller coefficients are calculated and updated online. The experimental results demonstrate that the ARC tracks a variable frequency signal very effectively and results in very low THD of input current under steady state.